Sammlung Franz West. - Loers, Veit (Innsbruck : Galerie im Taxispalais, 1995)
LeWitt, Sol ; West, Franz ; Pistoletto, Michelangelo ; Kippenberger, Martin ; Wiegand, Hans ; Senn, Gabi ; Brandl, Herbert ; Prini, Emilio ; Trautmannsdorff, Oktavian ; Zitko, Otto ; Schaerf, Eran ; Fuchs, Herbert ; Kogler, Peter
Sammlung Franz West, Galerie im Taxispalais, Innsbruck, 1995
boek